Comprehensive analysis of 124 transcriptomes from 31 tissues in developing, juvenile, and adult Japanese Black cattle. (1st September 2022) - Arishima, Taichi; Wakaguri, Hiroyuki; Nakashima, Ryotaro; Sakakihara, Seigo; Kawashima, Keisuke; Sugimoto, Yoshikazu; Suzuki, Yutaka; Sasaki, Shinji
Abstract: Omic analyses of economically important animals, including Japanese Black cattle, are currently underway worldwide. In particular, tissue and developmental stage-specific transcriptome characterization is essential for understanding the molecular mechanisms underlying the phenotypic expression of genetic disorders and economic traits. Here, we conducted a comprehensive analysis of 124 transcriptomes across 31 major tissues from fetuses, juvenile calves, and adult Japanese Black cattle using short-read sequencing. We found that genes exhibiting high tissue-specific expression tended to increase after 60 days from fertilization and significantly reflected tissue-relevant biology. Based on gene expression variation and inflection points during development, we categorized gene expression patterns as stable, increased, decreased, temporary, or complex in each tissue. We also analysed the expression profiles of causative genes (e.g. SLC12A1, ANXA10, and MYH6 ) for genetic disorders in cattle, revealing disease-relevant expression patterns. In addition, to directly analyse the structure of full-length transcripts without transcript reconstruction, we performed RNA sequencing analysis of 22 tissues using long-read sequencing and identified 232 novel non-RefSeq isoforms. Collectively, our comprehensive transcriptomic analysis can serve as an important resource for the biological and functional interpretation of gene expression and enable the mechanistic interpretation of genetic disorders and economic traits in Japanese Black cattle.